Desain Teras Reaktor High Temperatur Gas-Cooled Reactor (HTGR) Model Mesh Triangular Dua Dimensi Berbahan Bakar Thorium Berpendingin Gas CO2 - Nasta Melia Dilaga; Yanti Yulianti; Agus Riyanto (Jurnal Teori dan Aplikasi Fisika, 2019)
The research of design reactor HTGR cell core with two dimensional triangular mesh model using thorium fueled and CO2 coolant has been done. Objective of the research was design critical condition of HTGR cell core so as obtained critical condition and high thermal power. The neutronic analyzed by CITATION of SRAC on 1/6 of reactor cell core. The parameter which analyzed were core fuel enrichment, size and configuration reactor cell core, critically and power density. The result was obtained the ideal reactor design with size (x) 202 cm and (y) 101 cm. The enrichment of first region was 3% and second region was 2.731%. The total thermal power of reactor was 100 MWth, maximum power density of reactor was 107.5371 Watt/cc and keff of reactor was 1.000008.